Application of central composite design in the Adsorption of Ca(II) on Metakaolin Zeolite - Guyo, Upenyu; Phiri, Lycenter Yard; Chigondo, Fidelis (Hindawi Publishing Corporation, 2019)
Metakaolin zeolite-A was synthesized from thermally activated kaolin clay and characterized by Fourier Transform Infrared Spectroscopy and X-Ray Diffraction Spectroscopy. The effects of pH (2–10), contact time (10–180 min), initial concentration (5–120 mgL−1), and dosage (0.1–2 g) and their interactions were investigated using response surface methodology following a central composite design. Optimum removal (87.70%) was obtained at pH 6, contact time 180 min, initial concentration 40.0 mgL−1, and adsorbent dosage 1.0 g by Excel Solver using the GRG solving method. The adsorption data fitted best to the Langmuir model with correlation coefficient 𝑅2 = 0.993 and Chi-square value 𝜒2 = 4.76. The Freundlich isotherm gave a correlation coefficient 𝑅2 = 0.933 and 𝜒2 = 37.91. The adsorption process followed the pseudo-second-order model. The calculated thermodynamic parameters showed that the adsorption process was endothermic and not thermodynamically spontaneous. The studied zeolite-A can therefore be used as a promising adsorbent for the removal of Ca(II) ions from aqueous solutions.